2019
DOI: 10.1002/ange.201909815
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Lead‐Free Hybrid Double Perovskite Crystals of (BA)2CsAgBiBr7 with Large Mobility‐Lifetime Product toward X‐Ray Detection

Abstract: Halide double perovskites have recently bloomed as the green candidates for optoelectronic applications,such as Xray detection. Despite great efforts,the exploration of promising organic-inorganic hybrid double perovskites towardX-ray detection remains unsuccessful. Now,s ingle crystals of the lead-free hybrid double perovskite,( BA) 2 CsAgBiBr 7 (BA + is n-butylammonium), featuring the unique 2D multilayered quantum-confined motif,e nable quite large mt (mobilitylifetime) product up to 1.21 10 À3 cm 2 V À1 .T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The dynamic response of such detector to an X-rays from an Ag-targeted tube at 50 kVp, turned on and off is shown in Figure 8a. In the following years different kinds of PSCs, that is, hybrid [47,50,51,[87][88][89] and inorganic [52] lead-halide, lead-free [67,[90][91][92][93] perovskites have been demonstrated as active layer for X-and γ-rays and α-particles detectors. The top X-ray detection performance reported so far for a PSCs-based device was reported by Wei et al, [51] who demonstrated that a Cl − dopant compensation of p-type MAPbBr 3 SC results in a significant improvement of both bulk resistivity and hole mobility, enhancing thus the charge collection efficiency maintaining low dark currents.…”
Section: (14 Of 26)mentioning
confidence: 99%
“…The dynamic response of such detector to an X-rays from an Ag-targeted tube at 50 kVp, turned on and off is shown in Figure 8a. In the following years different kinds of PSCs, that is, hybrid [47,50,51,[87][88][89] and inorganic [52] lead-halide, lead-free [67,[90][91][92][93] perovskites have been demonstrated as active layer for X-and γ-rays and α-particles detectors. The top X-ray detection performance reported so far for a PSCs-based device was reported by Wei et al, [51] who demonstrated that a Cl − dopant compensation of p-type MAPbBr 3 SC results in a significant improvement of both bulk resistivity and hole mobility, enhancing thus the charge collection efficiency maintaining low dark currents.…”
Section: (14 Of 26)mentioning
confidence: 99%
“…Fore xample,X ua nd co-workers fabricated a10mmsized 2D double perovskite single crystal based on the organic cations of BA + (C 4 H 9 NH 3 + )a nd achieved as ensitivity of 4.2 mCGy air À1 cm À2 . [17] Ji et al fabricated 3mms ized (BA) 2 EA 2 Pb 3 Br 10 (EA = HOC 2 H 4 NH 3 ) single crystals with an ultrahigh sensitivity of 6.8 10 3 mCGy air À1 cm À2 . [18] An alternative to the monoammonium cations reported so far is the employment of diammonium cations to form AA' nÀ1 M n X 3n+1 type 2D perovskites.T hese ditopic cations have two positive ends which act as bridges to electrostatically interact with the [MX 6 ] 2À slabs in the stacking direction.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Simultaneously, two-dimensional halide double perovskites with various compositions and performances have been rationally constructed by taking the advantage of the structure tunability. [8] Subsequently, high-performance X-ray detection and polarization-sensitive photodetection were achieved in (C 4 H 9 NH 3 ) 2 CsAgBiBr 7 [9] and (isopentylammonium) 2 CsAgBiBr 7 , [10] respectively. These prominent results enable lead-free double perovskites to be promising in optoelectronic application.…”
mentioning
confidence: 99%